2008
DOI: 10.1002/pssb.200844044
|View full text |Cite
|
Sign up to set email alerts
|

Cr‐related energy levels and mechanism of Cr2+ ion photorecharge in ZnS:Cr

Abstract: It is shown that published data and interpretation concerning the energy and origin of Cr‐related defects in ZnS:Cr as well as the mechanism of the Cr2+ → Cr+ photorecharge are ambiguous and contradictory. New data concerning these questions obtained by means of photodepolarization (PDP) spectroscopy methods for the first time are given. Several peaks of the impurity photocurrent are revealed in the PDP spectrum of ZnS:Cr thin‐film structures, which was measured from 0.7 eV to 3.9 eV. Two peaks are due to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 19 publications
1
40
0
Order By: Relevance
“…15 electroluminescence in the Cr:ZnS(Se) thin-film structure under AC excitation (ACTFEL). The strong increase of the Cr 2+ emission intensity proportional to Q 6 was reported in [102], where Q is the charge transferred through the EL film for the applied voltage cycle.…”
Section: Electrical Excitation Of the Transition Metals In Semiconducmentioning
confidence: 87%
“…15 electroluminescence in the Cr:ZnS(Se) thin-film structure under AC excitation (ACTFEL). The strong increase of the Cr 2+ emission intensity proportional to Q 6 was reported in [102], where Q is the charge transferred through the EL film for the applied voltage cycle.…”
Section: Electrical Excitation Of the Transition Metals In Semiconducmentioning
confidence: 87%
“…It can be observed that the ZnS:Cr 2+ materials obtained by different methods both show interesting flat and broadband luminescence in the waveband of 1700‐2900 nm with the FWHM of ~690 nm under the excitation of a 1480 nm laser diode. The Mid‐IR emission can be attributed to the typical transition of tetrahedrally coordinated Cr 2+ : 5 E → 5 T 2 . It is noteworthy to note that the emission intensity of samples obtained by hydrothermal process (purple line) and high‐temperature solid‐phase reaction method (green line) is different: the intensity of the green line has a sharp rise compared with the purple one.…”
Section: Resultsmentioning
confidence: 93%
“…The Mid-IR emission can be attributed to the typical transition of tetrahedrally coordinated Cr 2+ : 5 E → 5 T 2 . [24][25][26] It is noteworthy to note that the emission intensity of samples obtained by hydrothermal process (purple line) and high-temperature solid-phase reaction method (green line) is different: the intensity of the green line has a sharp rise compared with the purple one. In our experiment, H 2 O and organic solvents were used in hydrothermal synthesis process.…”
Section: Resultsmentioning
confidence: 99%
“…The lower symmetry results in a longwavelength shift of the band. Cr 2+ ions with the lowest local symmetry are predominant obviously in highly doped Cr:ZnS films because of increasing the number of charged defects, in particular of [Cr Zn + ] − acceptors [16].…”
Section: Resultsmentioning
confidence: 99%